Rekontruksi Ajaran Sufistik Era Medsos (Kajian Konsep Zuhud) - Wijaya, Roma (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractThe dynamics of contemporary phenomena that occur today are so many of the emergence of the moral degradation of spirituality. With the development of technology, the doctrine of Sufism has been adjusted so that it can be accepted by the general public and becomes a counter to the negative impacts of social media so that it can be interpreted in the era of social media. This study explores the concept and contextualization of zuhud. Through the descriptive and interpretative analysis method, the analysis describes the basic meaning of the concept of zuhud, then looks at its development and is related to the era of social media. The sources used are various studies on zuhud in journals, books, and so on, as well as the elaboration of references on digital technology, especially social media platforms. The results of this study are first the meaning of zuhud, which is defined as a spiritual capital that is not excessive. Second, the contextualization of zuhud is understood in the era of the development of information technology, especially social networking platforms, it means social media as needed.Keywords: Contextualization; Social media; Zuhud concept.AbstrakDinamika fenomena kekinian yang terjadi saat ini begitu banyak munculnya degradasi moral spiritualitas. Dengan berkembangnya teknologi, ajaran tasawuf telah disesuaikan agar dapat diterima oleh masyarakat luas dan menjadi counter terhadap dampak negatif media sosial sehingga dapat dimaknai di era media sosial. Kajian ini mengeksplorasi konsep dan kontekstualisasi zuhud. Melalui metode analisis deskriptif dan interpretatif, analisis tersebut mendeskripsikan makna dasar dari konsep zuhud, kemudian melihat perkembangannya dan dikaitkan dengan era media sosial. Sumber yang digunakan adalah berbagai kajian tentang zuhud dalam jurnal, buku, dan sebagainya, serta penjabaran referensi tentang teknologi digital khususnya platform media sosial. Hasil penelitian ini pertama adalah pengertian zuhud yang diartikan sebagai modal spiritual yang tidak berlebihan. Kedua, kontekstualisasi zuhud diaplikasikan di era perkembangan teknologi informasi, khususnya platform jejaring sosial, artinya media sosial sesuai kebutuhan yang adaptabel.Kata Kunci: Kontekstualisasi, Konsep zuhud, Media sosial.